does ln 1/e^6 = -6 convert into 1/e^6 = e ^-6 ???
Follow Math Help Forum on Facebook and Google+
Correct
Originally Posted by blondedude092 does ln 1/e^6 = -6 convert into 1/e^6 = e ^-6 ??? Assuming you were trying to write , yes you are correct
In general, ln(a)= b is the same as (converts into) so, in particular, , because and b= -6.
As an alternative we could say ln1/e^6 = ln1-lne^6 =0-6 = -6
Originally Posted by biffboy As an alternative we could say ln1/e^6 = ln1-lne^6 =0-6 = -6 I don't want to pick at you but to be exact ln1/e^6 = 0
View Tag Cloud